Hatching command in Autocad - Abdukalikova G.M., Абдукаликова Г.М.; Bisekesh A.M., Бисекеш А.М. (Рroblems of engineering and professional education, 2023)
Hatching is created to emphasize some details of this object. In the Autocad system, hatching is divided into types and types of its arrangement. In this article, we will consider all these and other complex primitives of the "Strichovka" command.